2019
DOI: 10.5114/pjp.2019.87101
|View full text |Cite
|
Sign up to set email alerts
|

Association of breast cancer grade with response to neoadjuvant chemotherapy assessed postoperatively

Abstract: Currently, breast cancer chemotherapy response can be predicted based on various parameters, with common reporting of tumour grade and Ki67 proliferation index. We analysed their association with pathological complete response (pCR) in a multivariate approach. The study was carried out in a group of 353 patients, treated by preoperative chemotherapy and prospectively observed. In selected patients, parallel to routing core needle biopsy assessment, gene expression profile of tumour was analysed by oligonucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Diaz-Casas et al reported the pCR rate as 21.3% in grade 3 tumors [31]. In the study of Jarzab et al, the pCR rate was reported as 30.9% in patients with grade 3 nuclear differentiation [32].…”
Section: Discussionmentioning
confidence: 96%
“…Diaz-Casas et al reported the pCR rate as 21.3% in grade 3 tumors [31]. In the study of Jarzab et al, the pCR rate was reported as 30.9% in patients with grade 3 nuclear differentiation [32].…”
Section: Discussionmentioning
confidence: 96%
“…Tumor grade 3 versus the other grades was associated with pCR (OR 6.36, p = 0.004). In univariate analysis, tumor grade was noticeably associated with pCR status in patients with G1 and G2 tumors, where pCR rarely occurs, while 31.3% of G3 tumors had pCR ( p < 0.0001) [ 31 ]. Finally, in 2019, Diaz-Redondo et al, in a HER2+ cohort of 259 patients treated with NAC-Trastuzumab ± Pertuzumab, determined that histological grade 3 was significantly related to pCR in a multivariate analysis [ 32 ].…”
Section: Predictive Factors Of Pathological Complete Responsementioning
confidence: 99%
“…16 Grade 3 tumours have a higher rate of pCR. 17 Pathological CR rates have been noted to be significantly higher in tumours with pre-treatment Ki67 >50%. 18 High TILs (>59%) is associated with higher pCR rates in all breast cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%